Non Motor Symptoms In Patients With parkinson's Disease In Baghdad Hospitals - Muslim, Ahmed Tahseen (AL-Kindy College Medical Journal, 2017)
Background:Parkinson’disease(PD) is a neurodegenerative disorder of the central nervous system characterized by resting tremor, bradykinesia, cogwheel rigidity, and impairment of postural reflexes; the frequency of PD increases with aging.Clinically Parkinson's disease characterized by two groups of symptoms: motor and non-motor symptoms.Non-motor symptoms can be categorized as autonomic, cognitive/psychiatric (may include depression, dementia, anxiety, hallucinations), sensory and rapid eye movements (REM) sleep behavior disorder (RBD).Objectives:The objectives of this study are to find out the frequency of the non-motor symptoms of idiopathic Parkinson disease in a group of patients in Baghdad hospitals.Type of the study:A cross sectional study with analytic elements,Methods: It was conducted in movement disorders clinic in neuroscience hospital, outpatient clinic at Baghdad teaching hospital and AL-Kadhumain teaching hospital during the period between the 1st. of December 2013 through July 2014. One hundred and two patients diagnosed as idiopathic Parkinson disease by a consultant neurologist..Results:The study found that the mean age of patients with Idiopathic Parkinson disease was 60 years. Among them, two thirds of patients (68/102) were males, and 55 %      (56/102) of patients were in advanced stage of the disease. The study also mentioned the percentage of non-motor symptoms of Idiopathic Parkinson disease and they ranged from the most frequent symptom[constipation(80%)] to the least frequent[bowel incontinence(16%)].Also the study shows the distribution of symptoms according to gender and the study found no significant difference between males and females. The study finds that there is no significant difference in symptoms development along the period of disease progression except for bowel incontinence [30.4 % (14/46) in early disease progression compared to 3.6 %( 2/56) in advanced disease] and sexual interest [34.8 %( 16/46) in early disease progression compared to3.6 (2/56) in advanced disease].Conclusions:Non motor symptoms of Parkinson disease is so frequent and represent a major burden on patients' quality of life and the study recommends a more concentration on them in the future